PENGARUH RETURN ON ASSET (ROA), LEVERAGE, DAN INTENSITAS MODAL TERHADAP PENGHINDARAN PAJAK (TAX AVOIDANCE) - Rosa, Hielda Faristria; Hartono, Arif; Ulfah, Ika Farida (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2022)
This study aims to examine the effect of Return On Assets, Leverage, and Capital Intensity on Tax Avoidance. The population in this study were all pharmaceutical companies listed on the Indonesia Stock Exchange during the 2017-2019 period, namely 10 companies. Sampling in this study using the purposive sampling method, in order to obtain 6 companies that meet the criteria. Regression analysis in this study using Multiple Linear Regression Analysis. Meanwhile, to test the hypothesis using the t-test and F-test. The results of this study partially show that the first hypothesis of the Return On Assets variable has no effect on tax avoidance. This means, if the Return on Assets decreases, the company tends to do tax avoidance. The second hypothesis is that the Leverage variable has an effect on Tax Avoidance. This means that if Leverage increases, the company tends to do Tax Avoidance. The third hypothesis is that the Capital Intensity variable has an effect on Tax Avoidance. This means, if there is an increase in capital it will cause the company to tend to do tax avoidance. The fourth hypothesis is that Return on Assets, Leverage, and Capital Intensity simultaneously affect the practice of Tax Avoidance with an R2 value of 56.8%. This shows the effect of all these variables is 56.8% on the Tax Avoidance variable.